Pengaruh e-leadership dan e-culture terhadap produktivitas kerja yang dimediasi oleh work engangement - Ningsih, Fidia; Suryosukmono, Gerry (Distribusi - Journal of Management and Business, 2024)
Digital transformation requires organizations to adapt to technological developments so that their organizations can survive in the future. The aim of this research is to determine the impact of e-leadership and e-culture on work productivity through work engagement. The type of research used is associative research with a quantitative approach. The sampling technique uses simple random sampling technique. The samples in this research were employees in two technical implementation units under the Ministry of Law and Human Rights in the Bengkulu area, namely the Class IIB Bengkulu Women's Correctional Institution and the Class II Bengkulu Special Development Institution for Children. The total sample in this study was 120 employees. This research uses a questionnaire as the main method of data collection. The analysis method uses SEM-PLS. Based on research results, e-leadership has a positive and significant effect on work productivity with a t-value of 3.977 and a P-value of 0. E-leadership also has a positive and significant effect on work engagement with a t-value of 2.97 and P- value of 0.003. Furthermore, e-culture has a positive and significant effect on work productivity with a t-value of 2.326 and a P-value of 0.02. For the influence of e-culture on work engagement, the influence of work engagement on work productivity, the indirect influence of e-Leadership on work productivity through work engagement and the indirect influence of e-culture on work productivity through work engagement in this study were stated to not have a positive influence and significant.